Make yourselves scarce: The effect of demographic change on the relative wages and employment rates of experienced workers - Michael J. Böhm; Christian Siegel (University of Kent, School of Economics, 2019)
We argue that rising supply of experience not only reduces experienced workers' relative wages but also their relative labor market participation. From a theoretical model we derive predictions which we quasi-experimentally investigate, using variation across U.S. local labor markets (LLMs) over the last decades and instrumenting experience supply by the LLMs' age structures a decade earlier. We find that aging substantially reduces experienced workers' relative wages and employment rates, and also their labor market participation rates. Our results imply thatthe effect of demographic change on labor markets might be more severe than previously recognized, as it reaches beyond wages.
Keywords: J11; J21; J31; 330; Demographic Change; Employment of Experienced Workers; Return to Experience